PENGARUH FAKTOR MODERASI TERHADAP HUBUNGAN ANTARA AUDIT TENURE DENGAN KUALITAS AUDIT PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - Harefa, Kanaya Sandra; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2024)
This study aims to examine the relationship between audit tenure and audit quality, based on the assumption that longer tenure is detrimental to audit quality; yet, the evidence from investigations of this assumption is inconclusive. This study also examines the effect of moderating factors on the relation between audit tenure and audit quality. The moderating factors are affiliation group and audit fees. The population in this study are nonfinancial companies listed on the Indonesia Stock Exchange from 2016 to 2022. Purposive sampling is used for selecting the sample of the study and 125 companies for 7 years were obtained as research sample. The hypothesis are tested using multiple linear regression analysis and interaction test to determine the effect of the moderating factors. This study finds that longer auditor tenure generally enhanced audit quality among Indonesian companies. However, affiliation group and audit fees as the moderating factors, negatively affect the relationship between audit tenure and audit quality. Results suggest that regulations limiting auditor tenure would be beneficial only to the shareholders of a narrow group of firms; while for the majority of firms, limiting auditor tenure may actually be counter-productive.